Erdély és a Partium a magyar hadtörténelemben - Nagy, Miklós Mihály (Közép-Európai Közlemények, 2016)
Hungarian military history is geographically tied to the Carpathian Basin, as the battles that determined the long-term fate of the Hungarian nation were fought in this geographical region, though Hungarians had also fought a great number of battles outside this area. Due to the physical geography of the Carpathian Basin, certain regions played a more important role than others in Hungarian military history. One of these special regions was Transylvania, which along with the adjacent Partium, became a symbol of the independent Hungarian state during the Ottoman rule. In addition, Transylvania, with its unique geographical separateness constituted a distinct sub-theater during the major wars of independence the Hungarians fought. The battles fought here generally did not have a great impact on the wars of independence, but they still influenced the outcomes. Thus Transylvania and Partium provide a special illustration of history and military geography, one which is inseparable from the Carpathian Basin. The present study discusses the geographical factors that made Transylvania a constant sub-theater of war in Hungarian military history. At the same time, it also describes the region’s geography, touching on how this seemingly peripheral area became an independent power center during certain historical periods.